Kas ir ką iš tiesų veikia Henriko Radausko poezijoje - Peluritytė-Tikuišienė, Audinga (Literatūra, 2010)
The hermetic Henrikas Radauskas’ poetic world unfolds as a chrestomathic model of a world-view of the modernity. Beauty is the central intrigue that excites the poet, leading him to a philosophic adventure: to know death. The poet and his alter ego are constantly troubled by the lust for beauty, and they resolve to grasp the source of the substance that rules beauty and lust. The space of personal phantasy is reached during the moment of philosophical adventure, and it is analysed in this article invoking the thoughts of philosophers of postmodernity – Alphonso Lingis, Jacques Lacan, Slavoj Žižek, Audronė Žukauskaitė. And although one can strike some endearing and mortal revelations of feminine forms of substance in Radauskas’ creation, the most characteristic would be the Sleeping Beauty, Aphrodite and Venus. The eloquent figure of Poet, Satan, Pan occupies the place of Master in this creation. It is interesting that in the process of matter transformation these figures does not have power to approach the central mystery that interests poet Radauskas – the source of life, but are suitable to ask questions about the proportion of death and beauty in the nature world.Roaring experiences of beauty and death guides the poet’s thought into a deeper field of knowledge. In order to name it one should invoke the parameters of classical philosophy. Since the poet himself does not answer to such questions in any other way but by poetry texts, one needs to search for clues in plots of antique myths, tales and antique philosophy that interests him. A model of antique couple of Aphrodite and Hephaestus which at least motivates the questions that interest the poet (on life and death, on sources of nature, on source of beauty) is invoked in the article. Radauskas’ creation is architectonic, based on a conception of limit and balance. This conception is impersonated by Hephaestus’ look onto nature and things, which tempers and limits Aphrodite’s influence on the world. An especially influent, dynamic and eloquent verb impersonates dynamic Hephaestus’ look. It also creates the entire world of phantasy.